Enhancing the catalytic performance of cobalt oxide by doping on ceria in the high temperature water-gas shift reaction - Jha, Ajay; Jeong, Dae-Woon; Lee, Yeol-Lim; Nah, In Wook; Roh, Hyun-Seog (ROYAL SOC CHEMISTRY, 2015)
The high temperature water-gas shift (HT-WGS) reaction was performed using a Co-CeO2 catalyst, prepared through a co-precipitation method. The catalyst showed stable activity performance at 400 degrees C with 90% CO conversion without any side reactions (methanation) at a very high GHSV of 143 000 h(-1), which is the highest value reported for the HT-WGS reaction. This remarkable performance is attributed to the superior reducible nature of ceria and the preferential exposure of (220) and (112) facets of CeO2 and Co3O4, respectively. The time-on-stream study substantiates that ceria stabilizes the surface area of the Co-CeO2 catalyst during the WGS reaction compared to the bulk Co3O4.
Keywords: METAL-OXIDE; SOLID-SOLUTIONS; OXIDATION; CO3O4; MORPHOLOGY; INTERFACE; CHEMISTRY; HYDROGEN; ETHANOL; METHANE